A 3D‐Bioprinted Multiple Myeloma Model (Adv. Healthcare Mater. 7/2022). Issue 7 (6th April 2022) - Wu, Di; Wang, Zongyi; Li, Jun; Song, Yan; Perez, Manuel Everardo Mondragon; Wang, Zixuan; Cao, Xia; Cao, Changliang; Maharjan, Sushila; Anderson, Kenneth C.; Chauhan, Dharminder; Zhang, Yu Shrike
Abstract : Coaxial Extrusion In article number 2100884 by Kenneth C. Anderson, Dharminder Chauhan, Yu Shrike Zhang, and co‐workers, a high‐content in vitro model of multiple myeloma is produced using a coaxial extrusion bioprinting method, allowing formation of a human bone marrow‐like microenvironment featuring an outer mineral‐containing sheath and an inner soft hydrogel‐based core. The embedded myeloma cells reveal favorable characteristics of growth kinetics and drug responses, providing potential new insights for myeloma modeling, drug development, and personalizable therapy.